Bomb the base in the bus: Public transport as intersections of a local popular culture in Padang, Indonesia - Jones, Tod (Routledge: Taylor and Francis Group, 2008)
Most research into consumption and popular culture in Indonesia has been focussed on the middle and upper classes who have been characterised as opting for a consumption-based culture over traditional ways of life. However, this paper on popular culture in Padang, West Sumatra, demonstrates that consumption is also an important element of working class Indonesians' lives. The angkutan (modified vans used for public transport) and bis kota (city buses) in Padang in the Indonesian province of West Sumatra are brightly decorated with pictures and items depicting local and global themes. They are also equipped with expensive entertainment systems, produced by an expanding global marketplace, that broadcast local, Indonesian and foreign music in a variety of genres. In this paper, I explore the different factors that shape visual and musical expression on local transport. After providing a description of this popular cultural formation, I identify two constructions as the most prominent organising sensibilities: a youth culture that celebrates modernity and the culture of an older generation that emphasises an ongoing relationship to tradition and nature.